Strategi Inovatif Pengelolaan Sumber Daya Perikanan Laut: Peningkatan Kesejahteraan Nelayan Melalui Studi Kasus Di Perairan Desa Siofabanua, Nias Utara - Gea, Angel Sri Ayu; Zega, Asokhiwa; Telaumbanua, Betzy Victor; Zebua, Ratna Dewi; Laoli, Destriman (CV. SINAR HOWUHOWU, 2024)
This research explores innovative strategies in the management of marine fisheries resources and their impact on the welfare of fishers in Siofabanua Village, North Nias. Using a holistic and multidisciplinary approach, we analyzed aspects of the marine ecosystem, fishers' socioeconomic dynamics, and fisheries management policies. The analysis showed that the implementation of innovative strategies significantly improved fishers' income, access to education and health, and their quality of life. Government support, community involvement, and fishers' capacity also play an important role in the success of innovative strategies. This research provides recommendations for governments, non-governmental organizations and communities to strengthen policies, funding, institutions and cooperation to maintain the sustainability of marine fisheries resources and improve fishers' welfare. This article not only provides an in-depth understanding of the challenges faced by fishing communities in Siofabanua Village, but also proposes innovative solutions to improve their welfare. It is hoped that this article can serve as a guide for practitioners, policy makers, and communities in maintaining the sustainability of marine fisheries resources and the welfare of fishers in coastal areas.